2002
DOI: 10.1021/jf020391w
|View full text |Cite
|
Sign up to set email alerts
|

2,2‘-Diphenyl-1-picrylhydrazyl Radical-Scavenging Active Components from Adlay (Coix lachryma-jobi L. Var. ma-yuen Stapf) Hulls

Abstract: An activity-directed fractionation and purification process was used to identify the antioxidative components of adlay hulls. Hulls of adlay (Coix lachryma-jobi L. var. ma-yuen Stapf) were extracted with methanol and then separated into water, 1-butanol, ethyl acetate, and hexane fractions. The 1-butanol-soluble fraction exhibited greater capacity to scavenge 2,2'-diphenyl-1-picrylhydrazyl (DPPH) radicals when compared with fractions soluble in water, ethyl acetate, and hexane phases. The 1-butanol fraction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 27 publications
2
77
0
2
Order By: Relevance
“…The preparation of adlay extracts was from the previously described method, with minor modifications. 7 Adlay brans were blended in powder form and screened through a 20-mesh sieve (aperture 0.94 mm). The powder of adlay bran (100 g) was extracted with 1 l of methanol stirred on a stirring plate at room temperature for 24 h. Contents were filtered through #1 filter paper (Whatman Inc., Hillsboro, OR, USA).…”
Section: Reagentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The preparation of adlay extracts was from the previously described method, with minor modifications. 7 Adlay brans were blended in powder form and screened through a 20-mesh sieve (aperture 0.94 mm). The powder of adlay bran (100 g) was extracted with 1 l of methanol stirred on a stirring plate at room temperature for 24 h. Contents were filtered through #1 filter paper (Whatman Inc., Hillsboro, OR, USA).…”
Section: Reagentsmentioning
confidence: 99%
“…The solvent (water, butanol, ethyl acetate, n-hexane) was concentrated to dryness in vacuum condition to give dried powder and stored at À201C until use. ABM-Bu was further fractionated using Diaion HP-20 resin column chromatography with gradient Downregulation of progesterone biosynthesis by ABM S-M Hsia et al elution as previously described 7 and had 21 fractions assigned as A to U (Figure 1). For in vitro study, powders of adlay extracts were dissolved in DMSO to prepare stocks.…”
Section: Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Epidemiological and invitro studies suggested that plants are major constituent in antioxidant based drugs/ formulations used for the prevention of complex diseases. 4 The use of herbs in traditional way is becoming revitalized over the world. More over since modern medicine in becoming more wide spread but at a high cost.…”
Section: Iintroductionmentioning
confidence: 99%